CD-ROM guide to multimedia authoring (Chestnut Hill: AP Professional, 1995)
Interactive guide to creating multimedia products, including design, planning, storyboarding, and navigation. Demonstrates and teaches the entire design process for all platforms, including how to develop video to run across platforms, and how to track, connect, and display hyperlinks to topics in text, graphics, and video. Also includes exercises to help the user understand the macro and micro level issues involved in multimedia development.
Τίτλος από ετικέτα CD-ROM
System requirements for Macintosh: Macintosh computer with 68020 processor or better; 8MB RAM; CD-ROM drive
System requirements for PC: IBM PC with 386 processor or better; 8MB RAM; CD-ROM drive
System requirements for UNIX: BSD 4.2 or better; ISO-9660 compatible CD-ROM drive
Keywords: Interactive multimedia -- Authorship